A new species of striped Ichthyophis Fitzinger, 1826 (Amphibia: Gymnophiona: Ichthyophiidae) from Myanmar - Wilkinson, Mark; Presswell, Bronwen; Sherratt, Emma; Papadopoulou, Anna; Gower, David J. (Zootaxa, 2014)
A new species of striped ichthyophiid caecilian, Ichthyophis multicolor sp. nov., is described on the basis of morphological and molecular data from a sample of 14 specimens from Ayeyarwady Region, Myanmar. The new species resembles superficially the Indian I. tricolor Annandale, 1909 in having both a pale lateral stripe and an adjacent dark ventrolateral stripe contrasting with a paler venter. It differs from I. tricolor in having many more annuli, and in many details of cranial osteology, and molecular data indicate that it is more closely related to other Southeast Asian Ichthyophis than to those of South Asia. The caecilian fauna of Myanmar is exceptionally poorly known but is likely to include chikilids as well as multiple species of Ichthyophis.